Bankruptcy Prediction Analysis Using the Altman Z-Score, Zmijewski, Springate and Grover Methods at PT. Smartfren Telecom Tbk - Sakinah, Nur Novi Trianti; Muniarty, Puji (Jurnal Profita: Komunikasi Ilmiah Akuntansi dan Perpajakan, 2023)
Bankruptcy is a condition in which a company is unable to operate the company properly because the financial difficulties experienced are already very severe. Based on the analysis of PT.'s financial statements Smartfren Telecom, Tbk shows an alarming condition that is always experiencing losses and increasing the amount of debt. The purpose of this research is to find out the financial condition of PT. Smartfren Telecom, Tbk using Altman Z-Score, Zmijewski, Springate and Grover methods. The number of samples is 10 years with the period 2010-2019. This type of research is descriptive research using bankruptcy method and one sample t-test. The results of this study show altman Z-Score method, Zmijewski and Springate predict PT. Smartfren Telecom, Tbk has the potential to suffer another bankruptcy with Grover method that precisely predicts PT. Smartfren Telecom, Tbk is located in the grey area. While the results of the one sample t-test test showed altman Z-Score, Springate and Grover methods significantly did not have the potential to go into bankruptcy, this was due to the absence of problems in the company's total assets, sales and capital. As well as Zmijewski's method of insignificantly potentially experiencing bankruptcy, this is due to the company's poor revenue and debt. Based on the results of the standard deviation value shows that grover method is the most accurate method in predicting bankruptcy in PT. Smartfren Telecom, Tbk.